Improving forehand drop shot stroke skill in badminton through the drill method for children - Permata Sari, M.; Bagus Januarto, O.; Sugiarto, T. (Advances in Health Sciences Research, 2020)
The aimed of this research is to improve forehand drop shot stroke skill in badminton for 8-12 years old athlete in Brawijaya Jr. Badminton`s club Malang. This study uses the Sports Action Research (PTO) method using two tiered cycles covering planning, implementation, observation, reflection and with a qualitative descriptive approach. The research subjects were badminton athletes in PB. Brawijaya Jr. Malang City has 14 athletes. The results showed that the success rate of drop shot forehand in the first cycle was 60.7% from the 1st observer and 59% from the 2nd observer, while in the second cycle the success rate was 79.3% from the 1st observer and 80.1% from the observer 2. Conclusions this study shows that training using the drill method can improve the forehand drop shot badminton skills for athletes aged 8-12 years in PB. Brawijaya Jr. Malang city